Salivary biomarker responses to two final matches in women`s professional football - Maya, J.; Marquez, P.; Penailillo, L.; Contreras-Ferrat, A.; Deldicque, L.; Zbinden-Foncea, H. (Journal of Sports Science & Medicine, 2016)
The aim of this study was to examine the link between salivary concentrations of cortisol, testosterone, immunoglobulin A (IgA) and the rate of perceived exertion (RPE) as a measure of internal load after two final matches played 3 days apart by professional women football players. Saliva samples were taken before and after the two matches (M1, M2). RPE was used to monitor the exercise intensity after each match. Testosterone concentrations increased after each match (M1: +42%, p = 0.002; M2: +50%, p < 0.001) while cortisol increased only after M1 (+116%, p < 0.001). The testosterone-to-cortisol ratio decreased only after M1 (-32.4%, p < 0.001). IgA concentration did not change after any match. Testosterone concentrations were correlated with IgA concentrations after each match (M1: R = 0.59, p = 0.008; M2: R=0.51, p = 0.02). RPE was correlated with cortisol concentrations after M1 (R = 0.57; p = 0.01), but not after M2 (R = 0.38; p = 0.07). All these results suggest that salivary cortisol and testosterone concentrations increase especially after the first match of a final, without affecting IgA levels. We speculate that increased testosterone concentration in women after football matches may play a protecting role against immune suppression usually observed after intense exercise.